2009
DOI: 10.1002/pbc.21918
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of intestinal and hepatic mucormycosis in an immunocompromized child

Abstract: During ALL chemotherapy, a 4-year-old patient presented with febrile neutropenia and abdominal pain. Ultrasound examinations were repeatedly normal. Computerized tomography on day 7 demonstrated appendicitis and multiple hepatic foci identified as mucormycosis (Absidia corymbifera). Successful outcome was achieved by aggressive re-surgery, long-term antifungal therapy with serum level-monitored posaconazole, and recovery of neutrophil counts. Considering the interference of posaconazole with CYP3A4, vincristin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…To identify additional patients, we conducted an updated literature review of posaconazole oral suspension in paediatric patients younger than 13 years of age (see Table S1, Online Appendix/Supplemental Digital Content, which describes the identified publications). In our review of the literature, 10 publications were identified . For the indication of treatment, one prospective cohort study, four case reports and one retrospective cohort study described the use of posaconazole in 29 patients younger than 13 years of age using doses of 9–70 mg/kg/day.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To identify additional patients, we conducted an updated literature review of posaconazole oral suspension in paediatric patients younger than 13 years of age (see Table S1, Online Appendix/Supplemental Digital Content, which describes the identified publications). In our review of the literature, 10 publications were identified . For the indication of treatment, one prospective cohort study, four case reports and one retrospective cohort study described the use of posaconazole in 29 patients younger than 13 years of age using doses of 9–70 mg/kg/day.…”
Section: Discussionmentioning
confidence: 99%
“…In our review of the literature, 10 publications were identified . For the indication of treatment, one prospective cohort study, four case reports and one retrospective cohort study described the use of posaconazole in 29 patients younger than 13 years of age using doses of 9–70 mg/kg/day. Reported posaconazole concentrations ranged from 85 to 2160 ng/mL .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found seventeen cases of isolated hepatic mucormycosis in the literature [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27], of which the majority had hematologic malignancy with associated neutropenia and/or cytotoxic chemotherapy. We identified only four cases of isolated hepatic mucormycosis in solid organ transplant recipients, of whom three had liver transplants and one had a kidney transplant ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…7 Hepatic mucormycosis has been associated with direct ingestion of naturopathic medicine containing Mucor species and is well documented among neonatal patients. 8,9 Hepatic mucormycosis is readily seen on abdominal imaging. Typical CT findings include the presence of hypodense hepatic lesions surrounding vessels without a mass effect, representing areas of liver necrosis due to fungal thrombosis.…”
mentioning
confidence: 99%